The BcLAE1 is involved in the regulation of ABA biosynthesis in Botrytis cinerea TB-31 - Wei, Zhao; Shu, Dan; Sun, Qun; Chen, Dong-bo; Li, Zhe-min; Luo, Di; Yang, Jie; Tan, Hong (Frontiers in Microbiology, 2022)
Abscisic acid (ABA), as a classic plant hormone, is a key factor in balancing the metabolism of endogenous plant hormones, and plays an important role in regulating the activation of mammalian innate immune cells and glucose homeostasis. Currently, Botrytis cinerea has been used for fermentation to produce ABA. However, the mechanism of the regulation of ABA biosynthesis in B. cinerea is still not fully understood. The putative methyltransferase LaeA/LAE1 is a global regulator involved in the biosynthesis of a variety of secondary metabolites in filamentous fungi. In this study, we demonstrated that BcLAE1 plays an important role in the regulation of ABA biosynthesis in B. cinerea TB-31 by knockout experiment. The deletion of Bclae1 caused a 95% reduction in ABA yields, accompanied by a decrease of the transcriptional level of the ABA synthesis gene cluster Bcaba1-4. Further RNA-seq analysis indicated that deletion of Bclae1 also affected the expression level of key enzymes of BOA and BOT in secondary metabolism, and accompanied by clustering regulatory features. Meanwhile, we found that BcLAE1 is involved in epigenetic regulation as a methyltransferase, with enhanced H3K9me3 modification and attenuated H3K4me2 modification in ΔBclae1 mutant, and this may be a strategy for BcLAE1 to regulate ABA synthesis.